Interleukin-1 Receptor Antagonist Polymorphism and Birth Timing: Pathway Analysis Among African American Women. Issue 2 (March 2017) - Gillespie, Shannon L.; Neal, Jeremy L.; Christian, Lisa M.; Szalacha, Laura A.; McCarthy, Donna O.; Salsberry, Pamela J.
Abstract : Background: Timing of birth is a major determinant of newborn health. African American women are at increased risk for early birth, particularly via the inflammatory pathway. Variants of the IL1RN gene, which encode the interleukin-1 receptor antagonist (IL-1Ra) protein, are implicated in early birth. The biological pathways linking these variables remain unclear. Evidence also suggests that inflammatory pathways differ by race; however, studies among African American women are lacking. Objectives: We assessed whether an IL1RN variant was associated with timing of birth among African American women and whether this relationship was mediated by lower anti-inflammatory IL-1Ra production or related to a decrease in inhibition of proinflammatory IL-1β production. Methods: A candidate gene study using a prospective cohort design was used. We collected blood samples at 28–32 weeks of gestation among African American women experiencing an uncomplicated pregnancy ( N = 89). IL1RN single-nucleotide polymorphism (SNP) rs2637988 was genotyped, and lipopolysaccharide-stimulated IL-1Ra and IL-1β production was quantified. Medical record review determined timing of birth. Results: Women with GG genotype gave birth earlier than women with AA/AG genotypes ( b* = .21, p = .04). There was no indirect effect of IL1RN SNP rs2637988 allele status on timing of birth through IL-1Ra production, as evidenced by a nonsignificant product of coefficients in mediational analyses ( ab = .006, 95% CI [−0.05, 0.13]). Women with GG genotype showed less inhibition of IL-1β production for a unit positive difference in IL-1Ra production than women with AA/AG genotypes ( b* = .93, p = .03). Greater IL-1β production at 28–32 weeks of pregnancy was marginally associated with earlier birth ( b* = .21, p = .05). Discussion: Women with GG genotype may be at risk for earlier birth because of diminished IL-1β inhibition, allowing for initiation of a robust inflammatory response upon even mild immune challenge. Study of inflammatory contributions to early birth among African American women may be key to identifying potential prognostic markers of risk and targeted preventive interventions.